Potensi Penerimaan Pajak Penghasilan di Indonesia: Sebuah Analisis Deret Waktu - Sinurat, Ronaldo Putra Pratama (JURNAL PAJAK INDONESIA, 2023)
Income tax has an important role in state revenue. Optimization of income tax revenue will certainly make revenue in Indonesia will increase This study aims to analyze the potential for income tax revenue and the factors that influence it. Income tax potential is analyzed using the ARIMA (2,1,1) model, which shows that income tax potential tends to fluctuate and shows an increasing trend. In addition, multiple linear regression analysis was conducted by considering variables such as gross domestic product, exchange rate, inflation, and labor as independent variables. The analysis results show that, both simultaneously and partially, the four variables have a positive and significant influence on income tax revenue in Indonesia